A Design and Implementation of Local Festivals and Travel Information Service Application - 안재현(Jae Hyun Ahn); 이항주(Hang Ju Lee); 이세연(Se Yeon Lee); 한지원(Ji Won Han); 이원주(Won Joo Lee) (韓國컴퓨터情報學會論文誌, 2023)
In this paper, we design and implement the Walking Life Festival application, which is based on the Android platform and provides information about domestic travel destinations and regional festivals in South Korea. This application utilizes various sensors found in smartphones, including the Step Counter sensor, Step Detector sensor, Acceleration sensor, and GPS sensor. Additionally, it makes use of Google Map API and Public Open API to offer information about domestic travel destinations and local festivals. The application also incorporates an automatic login feature using the Shared Preference API. When storing login information in the database, it encrypts the input plaintext data using a hash algorithm. For Google Maps integration, it creates objects using the Google.maps.LatLngBounds() method and extends the location information through the extends method. Furthermore, this application contributes to the activation of the domestic tourism industry by notifying users about the timing of local festivals related to domestic travel destinations, thus increasing their opportunities to participate in these festivals. 본 논문에서는 안드로이드 플랫폼 기반의 국내 여행지 및 지역 축제 정보를 제공하는 Walking Life Festival 애플리케이션을 설계하고 구현한다. 이 애플리케이션은 스마트폰 내장 센서 중 걸음 횟수 센서(Step Counter Sensor)와 걸음 감지 센서(Step Detector Sensor), 가속도 센서(Acceleration Sensor), GPS 센서 등을 활용한다. 그리고 Google Map API와 Public Open API를 활용하여 국내 여행지 및 지역 축제정보를 제공한다. 이 애플리케이션은 Shared preference API를 사용하여 자동 로그인 기능을 구현한다. 그리고 로그인 정보를 데이터베이스에 저장할 때는 해시 알고리즘을 통해 입력된 평문 데이터를 받아서 암호화하여 저장한다. Google Map은 Google.maps.LatLngBounds() 메서드를 활용해서 객체를 생성한 후 extends 메서드를 통해 위치정보를 전송하도록 구현한다. 또한, 이 애플리케이션은 국내 여행지와 관련된 지역 축제 개최 시기를 알림으로써 축제 참여 기회를 높임으로써 국내 관광 산업 활성화에 기여한다.